Numerical analysis for thermal management of data center with phase change material - Öztop, Hakan Fehmi; Ozgul, Ridvan; Selimefendigil, Fatih (Emerald Group Publishing Ltd, 2022)
Purpose The purpose of this paper is to analyze the performance of a data center and thermal management by using phase change material (PCM). Numerical studies were conducted for two dimensional model of data center and installation of PCM at different locations. Design/methodology/approach Finite volume method was used for the unsteady problem, while impacts of air velocity and PCM location on the flow field, thermal pattern variations and phase change dynamics were evaluated. Three different locations of the PCM were considered while air velocity was also varied during the simulation. Thermal field variations and cooling performance of the system for different PCM location scenarios were compared. Findings It was observed that the installation of the PCM has significant impacts on the vortex formation, thermal field variation within the system and its performance. The left, right and top wall installation of the PCM changed the thermal patterns near the heat cell of the data centre. The phase change process is fast for the upper wall installation of the PCM, while the discrepancy of the melt fraction dynamics between different air flow at this position is minimum. The case where PCM placed in the upper wall at the highest air velocity is the best configuration in terms of heat storage. The utilization of PCM and changing its locations provide an excellent tool for thermal management and cooling performance of data centre. Originality/value Results of this study can be used for initial design and optimization of cooling systems for thermal management of data centers while the importance of the high-performance computing becomes very crucial for the advanced simulations in different technological applications.
Keywords: Thermal management; Data center; CFD; Thermal energy storage; Phase change material